subject
Mathematics, 08.11.2019 10:31 francisco42002

Explain why the question -2(3x+6)=6(x+2)

ansver
Answers: 1

Another question on Mathematics

question
Mathematics, 21.06.2019 13:40
Show algebraically that f and g are inverse functions f(x)=x^2/-6; g(x)=square root of 2x+12​
Answers: 1
question
Mathematics, 21.06.2019 17:30
How do you find principle and simple interest
Answers: 1
question
Mathematics, 21.06.2019 18:00
What are the equivalent ratios for 24/2= /3= /5.5=108/ = /15
Answers: 1
question
Mathematics, 21.06.2019 21:30
If f(x)=x+7 and g(x)=1/x what is (fog)(x)
Answers: 1
You know the right answer?
Explain why the question -2(3x+6)=6(x+2)...
Questions
question
Mathematics, 23.10.2020 18:00
question
English, 23.10.2020 18:00
question
History, 23.10.2020 18:00
question
History, 23.10.2020 18:00
question
Mathematics, 23.10.2020 18:00
Questions on the website: 13324936